Effects of exercise prior or during pregnancy in high fat diet fed mice alter bone gene expression of female offspring: An experimental study - Abbasali Gaeini; Mohamadreza Baghaban Eslaminejad; Siroos Choobineh; Neda Mousavi; Sadegh Satarifard; Leila Shafieineek (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Ovarian hyperstimulation syndrome (OHSS) is one of the most important complications of assisted reproduction treatment. Many substances are involved in the regulation of the vascular permeability, which have been concerned to cause OHSS. Vascular endothelial growth factor (VEGF) has emerged as one of the main angiogenic factors, which could be responsible for increased vascular permeability. Objective: In this study the association of vascular endothelial growth factor - 460C/T and +405 G/C polymorphisms and susceptibility to ovarian hyperstimulation syndrome was evaluated. Materials and Methods: In this cross sectional study, VEGF gene polymorphisms were amplified by Polymerase chain reaction- Restriction Fragment Length Polymorphism in 75 women with established OHSS (case group) and 85 normoresponder (control group) which received conventional ovarian stimulation regimen. Results: There was no significant difference in the frequency of -460 C/T polymorphism between cases and controls (p=0.85). The frequency of +405 G/C polymorphism was significantly higher in the OHSS women (p=0.03, OR=2.44; 95% CI=1.23-4.82). Conclusion: In women who developed OHSS, VEGF gene polymorphism +405 could be effective. Two of the polymorphisms -460 C/T and +405 G/C were reported to be associated with increased VEGF basal promoter activity. However, only +405 G/C gene polymorphisms were more frequent in cases than controls